(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: This article covers the use of modern methods in teaching foreign languages, the study of the main principles, pedagogical approaches and technological advances that have revolutionized language education. From communicative language teaching and task-based learning to the integration of digital tools and multidisciplinary strategies, chapters explore the transformative impact of contemporary methodologies on language acquisition, student engagement, and pedagogical outcomes. Using these innovative methods, educators can inspire a new generation of language learners to navigate the complexities of a rapidly changing world with confidence, fluency, and intercultural competence.